The ABO and Rhesus (Rh) Blood Groups Distribution among the Female Blood Donors in Tertiary Care Hospital, Karachi - Irshad, Zareen; Parween, Salma; Anwar, Muhammed; Shabbir, Asma; Sultan, Binish Arif (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVE: To find out the prevalence of ABO (A, B, AB, O) blood group and Rhesus (Rh) blood group among the female blood donors. METHODOLOGY: The study was carried out at Jinnah Postgraduate Medical Centre, Karachi, in the blood bank department, from January 2016 to December 2018. A total of 394 female blood donors were eligible and enrolled for blood donation. For the determination of blood grouping (ABO and Rh), an antigen-antibody agglutination test using a slide method was performed. Both forward (cell grouping) and reserve (serum) grouping were performed. The data were evaluated through statistical software; SPSS version 23.0. RESULTS: A total of 394 female blood donors were presented during the study, the ABO blood group distribution was 118 (29.9%), 132 (33.5%), 94 (23.9%), and 50 (12.7%) for blood groups A, B, O, and AB respectively. Rh positive blood group was found in 364(92.4%) and in 30(7.6%) was Rh negative. CONCLUSION: The present study concludes that the most prevalent ABO blood group among female donors in Karachi is “B” whereas “AB” is the least prevalent. In the Rh system, Rh positive is more common than Rh negative.